2016
DOI: 10.4103/0972-5229.183911
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of patients in neurological Intensive Care Units of India: A survey

Abstract: Context:The rehabilitation needs of the patients in neurological Intensive Care Units (ICUs) vary from that of a medical ICU patient. Early mobilization is known to improve the various neurological outcomes in patients admitted to neurological ICUs, although little is known about the practice pattern among physiotherapists. The mobilization practice pattern may vary significantly than that of developed countries due to the reasons of differences in training of professionals, availability of equipment, and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
4
1
1
Order By: Relevance
“…These findings are in line with those found by Nozawa et al [27], when they determined this professional profile throughout Brazil. Different profiles were found in the studies by Bhat et al [28] and Hale et al [29]. The first conducted in India, showed that more than half of its respondents had just graduated; however, 34% said they had a master's degree, almost 18 times the number found in our study.…”
Section: Physiotherapists' Profilecontrasting
confidence: 86%
See 1 more Smart Citation
“…These findings are in line with those found by Nozawa et al [27], when they determined this professional profile throughout Brazil. Different profiles were found in the studies by Bhat et al [28] and Hale et al [29]. The first conducted in India, showed that more than half of its respondents had just graduated; however, 34% said they had a master's degree, almost 18 times the number found in our study.…”
Section: Physiotherapists' Profilecontrasting
confidence: 86%
“…Neurological and/or motor deficits and/or musculoskeletal limitations that make mobilization impossible: they constitute contraindications in 3, paragraphs II, VI, VII, VIII, X and XII, which briefly state that the physiotherapist is responsible for evaluating, prescribing and carrying out the rehabilitation of critical patients but that the multidisciplinary team's assistance is essential for a differentiated assessment and safe mobilization [17,[28][29][30][31].…”
Section: Physiotherapists' Profilementioning
confidence: 99%
“…Independent t test was used to see the treatment effect between two groups for RR and SpO2. (16) IC stretch is performed actively by thoracic mobility exercises. Passively IC stretch can be performed by thoracic rotation, mid sternum rotation, lateral thoracic stretching, through thoracic mobility exercises as well as through manual stretching of IC spaces.…”
Section: Resultsmentioning
confidence: 99%
“…As pesquisas feitas nos bancos de dados resultaram em 70 artigos, dos quais 68 foram excluídos de acordo com os critérios de exclusão pré-estabelecidos anteriormente, sendo selecionados e avaliados 2 artigos (BHAT et al, 2016;HASHIM et al, 2012;SIBINELLI et al, 2015). Estes estão apresentados no quadro 1 a seguir, em ordem alfabética: Os artigos apresentados neste estudo (HASHIM et al, 2012;SIBINELLI et al, 2015) não relataram mudanças em relação ao nível neurológico dos pacientes.…”
Section: Resultsunclassified